The hygroscopic behavior of plant fibers: a review - Célino, Amandine; Freour, Sylvain; Jacquemin, Frederic; Casari, Pascal (Frontiers in Chemistry, 2014)
Environmental concern has resulted in a renewed interest in bio-based materials. Among them, plant fibres are perceived as an environmentally friendly substitute to glass fibres for the reinforcement of composites, particularly in automotive engineering. Due to their wide availability, low cost, low density, high-specific mechanical properties and eco-friendly image, they are increasingly being employed as reinforcements in polymer matrix composites. Indeed, their complex microstructure as a composite material makes plant fibre a really interesting and challenging subject to study. Research subjects about such fibres are abundant because there are always some issues to prevent their use at large scale (poor adhesion, variability, low thermal resistance, hydrophilic behavior). The choice of natural fibres rather than glass fibres as filler yields a change of the final properties of the composite. One of the most relevant differences between the two kinds of fibre is their response to humidity. Actually, glass fibres are considered as hydrophobic whereas plant fibres have a pronounced hydrophilic behavior. Composite materials are often submitted to variable climatic conditions during their lifetime, including unsteady hygroscopic conditions. However, in humid conditions, strong hydrophilic behaviour of such reinforcing fibres leads to high level of moisture absorption in wet environments. This results in the structural modification of the fibres and an evolution of their mechanical properties together with the composites in which they are fitted in. Thereby, the understanding of these moisture absorption mechanisms as well as the influence of water on the final properties of these fibres and their composites is of great interest to get a better control of such new biomaterials. This is the topic of this review paper.